Effect Of High Temperature On Yield Attributing Traits In Bread Wheat - Singh, Khajan; Sharma, SN; Sharma, Yogendra (Bangladesh Journal of Agricultural Research, 2011)
High temperature stress is major constraint to bread wheat (Triticum aestivum L. Em. Thell) production. Generation of information on the effect of high temperature stress on various traits may be helpful for developing thermotolerance bread wheat variety. An experiment was conducted on a set of 10 diverse genotypes, their 45 F1s and F2s for identification of high temperature stress genotype. The experiment was conducted under normal and late sown condition. The parent HD 2851, P8W 520, and HS 448, and the crosses HS 448 × PBW 520, UP 2614 × K 209 and PBW 520 × HD 2851 for grain yield per plant were least affected under late sown conditions. Heat stress intensity (Dvalue) clearly indicated that grain yield per pant biological yield per plant and grain yield per spike suffered revively under late sown conditions. Keywords: Bread wheat; heat susceptibility index; tolerant genotypes. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9270 BJAR 2011; 36(3): 415-426